Limited Interleukin-18 Response in Salmonella-Infected Murine Macrophages and in Salmonella-Infected Mice - Elhofy, Adam (American Society for Microbiology, 1999)
Optimal immune responses against an intracellular bacterial pathogen, such as Salmonella, involve the production of gamma interferon (IFN-γ), which activates macrophages. It has recently been suggested that, interleukin-18 (IL-18), in addition to IL-12, contributes to the induction of IFN-γ following infection. Given this hypothesis, an optimal host immune response against intracellular bacterial pathogens would include the induction of IL-18 secretion by macrophages due to Salmonella infection. We questioned whether Salmonella could induce macrophages to upregulate their expression of IL-18 mRNA and secretion of IL-18. With cultures of murine macrophages, we were surprised to find that infection by wild-type Salmonella dublin resulted in decreased expression of IL-18 mRNA and IL-18 secretion rather than an increase. Reduction of macrophage-derived IL-18 expression by wild-type Salmonella occurred early in the response, suggesting a direct effect. Furthermore, mice orally inoculated with wild-type Salmonella were shown to have reduced IL-18 mRNA expression at mucosal sites within hours postinoculation. Together these studies demonstrate Salmonella-induced reductions in IL-18 expression, suggesting that this intracellular pathogen may be capable of limiting a potentially protective immune response.